Analysis of Revisit Intention Through Memorable Tourism Experiences and Visitor Satisfaction Influenced by Visitor Engagement in Banyuwangi Tourism Destinations - Rumli; Astuti, Widji; Supriadi, Bambang (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study aims to examine the impact of visitor engagement on revisit intention, mediated by memorable tourism experiences and visitor satisfaction in tourism destinations across Banyuwangi Regency. This quantitative research employed a survey design, with a sample determined using convenience sampling. A total of 200 visitors participated in the study. Data were analyzed using structural equation modeling with an emphasis on path analysis and standard coefficients. The model met the required thresholds of 0.7 for Cronbach’s alpha and composite reliability, as well as 0.5 for average variance extracted, indicating strong validity and reliability. Path analysis showed direct effects of visitor engagement on memorable tourism experiences and visitor satisfaction, as well as significant effects of memorable tourism experiences and visitor satisfaction on revisit intention. Moreover, visitor engagement indirectly influenced revisit intention through both mediators. These findings offer insights into the factors shaping visitor loyalty and destination competitiveness, particularly within Banyuwangi’s tourism sector. Understanding the importance of visitor engagement and memorable experiences can help tourism stakeholders develop more effective strategies to enhance visitor satisfaction and encourage repeat visitation.